“Apple: Good Business, Poor Citizen”: A Practitioner’s Response - Newkirk, David (Journal of business ethics, 2018)
This paper was written in response to Etzioni’s “Apple: Good Business Poor Citizen” (J Bus Ethics, 2016, doi:10.1007/s10551-016-3233-4). It argues that Etzioni is correct in seeing the recent conflict between Apple and the FBI over cracking the San Bernardino shooter’s iPhone as requiring that considerations of national security be balanced against the rights of those it might impact. There are nonetheless critical questions about one must still ask: whose rights are curbed, to what degree, and how does a society decide which side to favor? More attention needs to be paid to the privacy of other iPhone users and, importantly, the burden that hacking the phone might impose on Apple, either impairing its brand value or compromising its business potential. Finally, by asking ‘who judges the balance?’, it questions whether labeling Apple a poor citizen is premature, as they had only begun challenging the FBI’s judgment through the judicial process.